Using Self-Efficacy and Reflection to Improve Piano Learning Performance - Suqi Dong; Genutė Gedvilienė (Education Sciences)
There are many influences on the piano playing learning process. Research on combining it with self-regulated learning (SRL) methods has rarely been reported. This study aimed to elucidate the complex relationships between social skills, anxiety, and self-efficacy (SE) in piano learning and performance contexts. The question of whether reflection enhances SRL effectiveness was also raised. The participants included 24 Chinese piano students, who were divided into three groups and received different emotional interventions. Over the course of an eight-week study program, the groups were exposed to different teaching methods. One group received positive emotional input designed to boost confidence, another group encountered negative emotional input that triggered stress, and a control group received a routine without emotional manipulation. The relationship between anxiety, self-efficacy, social skills, mood, and reflection were explained through quantitative academic performance results and qualitative return interviews. The results showed that self-efficacy was significantly negatively related to anxiety levels, while transient emotional states had minimal impact on immediate learning outcomes. Reflection, on the other hand, led to the increased effectiveness of SRL, which could quickly alleviate anxiety and increase self-efficacy by enhancing students’ reflective process after class. This study also highlights the complexity of the interplay between social skills and self-efficacy, as well as anxiety levels. These findings suggest that fostering self-efficacy and reflective practices in piano education can help manage student anxiety and improve learning outcomes, providing valuable insights for teaching strategies.